Modern requirements for education of teachers of technics and information in Poland - Roman Monko (Kazimierz Wielki University, 2019)
The profession of teacher in Poland, as it follows from the analysis of pedagogical literature, is creative, connected with the fulfillment of a social mission. It requires professional orientation, which is expressed by a certain level of formal education and its improvement in the process of various forms of retraining and advanced training, the presence of a system of various professional competences, motivation. It is of particular importance for future teachers of engineering and computer science! Application of interactive methods in teaching that optimizes the development of their skills, strengthens the creative process and critical thinking, Achieving common goals with other students and educators.